2013
DOI: 10.1016/j.jtcvs.2012.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of change in coexistent mitral regurgitation after aortic valve replacement

Abstract: Objective Management of intermediate degrees of mitral regurgitation (MR) during aortic valve replacement (AVR) for aortic stenosis remains controversial. We sought to evaluate the degree of reduction of MR in patients undergoing AVR, as well as the relationship between the pre-operative gradient across the aortic valve and the degree of reduction in MR. Methods We retrospectively analyzed demographic, intraoperative, and echocardiographic data on 802 patients that underwent AVR or aortic root replacement be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Besides such findings, however, we confirmed here that the co-existence of moderate to severe mitral regurgitation also impacted early survival in the surgical cohort, thus fueling the recent highly debated need for concomitant mitral surgery during AVR. 12 Female sex in AVR patients also proved an independent predictor of intraprocedural/postprocedural transfusions, despite the absence of differences in major vascular complications. The detrimental impact of perioperative transfusions on outcome in the surgical population has been well ascertained.…”
Section: Female-related Differences In Risk Profiles and Outcome Aftementioning
confidence: 98%
“…Besides such findings, however, we confirmed here that the co-existence of moderate to severe mitral regurgitation also impacted early survival in the surgical cohort, thus fueling the recent highly debated need for concomitant mitral surgery during AVR. 12 Female sex in AVR patients also proved an independent predictor of intraprocedural/postprocedural transfusions, despite the absence of differences in major vascular complications. The detrimental impact of perioperative transfusions on outcome in the surgical population has been well ascertained.…”
Section: Female-related Differences In Risk Profiles and Outcome Aftementioning
confidence: 98%
“…Seventy-eight percent of the TAVR patients had no MR or less than moderate MR at baseline. It is known that these patients show little regression or progression after TAVR [40,41]. On the other hand our study showed more improvement in subjects with higher MR grade before intervention (63%).…”
Section: Change In Mr Gradementioning
confidence: 38%
“…After completing the literature search protocol, 27 studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] with the total of 4452 patients were found to meet the inclusion criteria and were included in the analysis following thorough assessment ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Out of these, 23 studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 36 ] (n = 2497) contained specific data about MR before and after surgery. Three publications [ 20 , 21 , 37 ] reported only mortality and survival data and one [ 32 ] was specific about pre and postoperative mitral anulus dimensions.…”
Section: Resultsmentioning
confidence: 99%